An Energy Management System for Hybrid Energy Sources-based Stand-alone Marine Microgrid. (August 2019) - Zia, M F; Elbouchikhi, E; Benbouzid, M E H
Abstract: Microgrids are becoming a viable solution for satisfying energy demand of rural and remote areas. Indeed, energy demand of islands can be met by renewable energy sources, energy storage systems, and micro-conventional generation sources-based microgrid systems. The optimal scheduling of these energy sources requires an energy management system for microgrids. Bretagne region in France has huge potential in marine renewable energy sources. Therefore, islands in this region can use tidal turbines with other energy sources to meet their local energy consumption. A case study of stand-alone marine microgrid system for Ouessant island is proposed in this paper. The considered microgrid includes PV system, tidal turbine, diesel generator, and Li-ion battery. The architecture and optimal scheduling of the developed microgrid system is presented to reduce operating and maintenance costs. The developed energy management architecture can help microgrid systems planning for islands in the near future.